Using Fuzzy Neural Networks to Improve Prediction of Expert Systems for Detection of Breast Cancer - Guimarães, Augusto Júnio; Araújo, Vinicius Jonathan; Batista, Lucas de Oliveira; Souza, Paulo Vitor Campos; Araújo, Vanessa; Rezende, Thiago Silva (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2018)
Este artigo não possui resumo.